1991
DOI: 10.1357/002224091784995819
|View full text |Cite
|
Sign up to set email alerts
|

Diel migration and feeding patterns of the chaetognath, <I>Sagitta friderici,</I> off the west coast of South Africa

Abstract: The vertical distribution patterns of adult and juvenile Sagitta friderici were investigated over a 48 h period, using samples collected at different depth strata with an RMT 1 x 6 net.Juvenile chaetognaths were generally found at depths of less than 50 m throughout the day and night, and exhibited limited diel migration patterns. Adults, on the other hand, migrated more extensively and were generally found below 50 m during the day and scattered throughout the water column or near the surface at night. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 25 publications
4
37
2
Order By: Relevance
“…Literature indicates, less than 30% of chaetognaths are found with 1-3-preys in their guts (Sullivan, 1980;Stuart & Verheye, 1991;Vega-Pérez & Liang, 1992, Liang & Vega-Pérez, 1995. In this study, in average, less than 10% was found with food in their gut.…”
Section: Feeding Habitsmentioning
confidence: 43%
“…Literature indicates, less than 30% of chaetognaths are found with 1-3-preys in their guts (Sullivan, 1980;Stuart & Verheye, 1991;Vega-Pérez & Liang, 1992, Liang & Vega-Pérez, 1995. In this study, in average, less than 10% was found with food in their gut.…”
Section: Feeding Habitsmentioning
confidence: 43%
“…Satiation as the major factor contributing to the midnight sinking of chaetognaths has been reported for several species (Pearre 1973(Pearre , 1974Stuart & Verheye 1991;Gibbons 1994). Our results on the vertical distribution, the feeding intensity and the presence of unidentified food, point that satiation was probably among the reasons why chaetognaths left the surface to disperse and distribute deeper at midnight: after the intake of large quantities of food at 20:00, the specimens of S. enflata sank to deeper layers to digest their food (24:00) and this was confirmed by the increase in the proportion of the unidentified food remains in the gut contents.…”
Section: Discussionmentioning
confidence: 92%
“…The diel vertical migration (DVM) of zooplankton is a common phenomenon in all aquatic ecosystems, and chaetognaths have also adopted this behavior at least partly for feeding purposes (Pearre 1973;Stuart & Verheye 1991;Gibbons 1992Gibbons , 1994Øresland 2000). Despite the great importance of this phenomenon, there are only two references about the diel migration of chaetognath species such as Sagitta enflata (Grassi, 1881), S. minima (Grassi, 1881), S. setosa Müller, 1847 and S. friderici Ritter-Záhony, 1911 in the Mediterranean (Pearre 1974;Andreu 1992), while there are no attempts to relate this behavior to feeding.…”
Section: Introductionmentioning
confidence: 99%
“…Vertical distribution patterns of zooplankton are complex phenomena involving several categories of behaviours that change from species to species, and even from individual to individual, and depend on factors such as endogenous rhythms, age, sex and spawning (Wooldrige and Erasmus, 1980;Hammer, 1981;Orsi, 1986;Saint-Jean and Pagano, 1990;Stuart and Verheye, 1991;Hays, 2003). Vertical migrations of zooplankton are nearly ubiquitous in both freshwater and marine systems and thus are well documented in the literature (Enright, 1970;Schwassmann, 1971;Decoursey, 1983;Lampert, 1989;Neilson and Perry, 1990;Hays, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Many evolutionary hypotheses have been developed to explain the mechanisms behind zooplankton vertical migrations. Predator evasion (Zaret and Suffern, 1976;Gliwicz, 1986;Harding et al, 1986;Simard et al, 1986;Dodson, 1988;Bollens and Frost, 1989a,b;Giske et al, 1990;Neill, 1990;Stuart and Verheye, 1991;Yamaguchi et al, 2004) and longitudinal transport control (Brookins and Epifanio, 1985;Epifanio, 1988;Hill, 1991aHill, ,b,c, 1995 are currently the most favoured hypotheses. Enright (1977) also suggested that vertical migration provides metabolic advantages.…”
Section: Introductionmentioning
confidence: 99%